Considering the impact of structural adjustment policies on forests in Bolivia, Cameroon and Indonesia - Kaimowitz, D.; Erwidodo.; Ndoye, O.; Pacheco, P.; Balanza, P.P.; Sunderlin, William D. (1998)
A preliminary insight into how structural adjustment policies (SAPs) may have affected deforestation and forest degradation in the lowland tropical forests of Bolivia, Cameroon and Indonesia. It presents tentative hypotheses regarding how changes in prices, costs, incomes and government services associated with SAPs affect forests. The indirect effects of SAP's on forests resulting from changes in overall economic growth, inflation rates, employment and consumption are difficult to measure and predict. The experience of Cameroon and Indonesia indicate that SAPs that sucees in creating new off-farm employment opportunities probably reduce deforestation, while those that do not succeed have the opposite effect, but this is still inconclusive. There is little evidence that government spending restrictions associated with SAPs diminished governments' ability to promote sustainable forest management or control deforestation, largerly because there was minimal capacity in the first place. It remains to be seen whether SAPs will favour or hinder the development of such capacity in the future.